A kind of amphiphilic transparent antifouling coating and its preparation method and application
By hydrolysis of the silicate produced under acidic conditions, polycondensation of silicates formed into a silicon-based network, and polyether modified polydimethylsiloxane is introduced to prepare an amphiphilic transparent anti-fouling coating, which solves the problem of insufficient transparency and adhesion of anti-fouling coatings in the prior art, and achieves high transparency and excellent anti-fouling performance.
Patent Information
- Application Number
- CN202310999551.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-08-09
AI Technical Summary
The existing marine anti-fouling coatings have shortcomings in terms of transparency and adhesion, and it is difficult to meet the requirements of underwater vehicle visual windows and detection windows for high transparency and anti-fouling performance.
A silicon-based network formed by polycondensation of silicates formed by hydrolysis under acidic conditions was used, and polyether modified polydimethylsiloxane was introduced, and an amphiphilic transparent anti-fouling coating was prepared by ultrasonic dispersion treatment and room temperature curing.
It has achieved a transparent anti-fouling coating with high optical transparency and good adhesion to the substrate, and has excellent anti-fouling performance and good desorption ability.
Smart Images

Figure CN117025089B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of marine antifouling coatings, and in particular to an amphiphilic transparent antifouling coating and a preparation method and application thereof. Background Art
[0002] With the increasing development and utilization of marine resources, the detection accuracy of marine detection facilities and equipment has decreased due to fouling, and the problem of signal transmission inaccuracy has become increasingly serious. The traditional marine antifouling coating currently used is mainly prepared by adding antifouling resin to functional fillers, but this preparation method will cause the coating to lose its transparent properties. Therefore, it is necessary to develop a convenient antifouling coating preparation technology that can be applied to the surface of underwater vehicles such as visual windows, detection windows, underwater cameras, etc., which have high transparency requirements for the coating, to ensure the visibility of the window and the accuracy of the detection data.
[0003] For transparent marine antifouling coatings, Zhou Feng proposed a method for preparing transparent marine antifouling coatings in Chinese patent CN113004752A "A transparent marine antifouling coating and its preparation method and application". The method first prepares a bonding resin, then mixes the bonding resin, silane coupling agent, plasticizer and alcohol ether solvent to obtain a bonding resin solution, and mixes the bonding resin solution with an antifouling agent aqueous solution to obtain a transparent marine antifouling coating. The process of preparing the coating by this method is relatively complicated, and the process flow is not easy to control.
[0004] Shan Jianwen proposed a method for preparing a transparent antifouling coating for glass in Chinese patent CN105152546A "A transparent antifouling coating material for glass, a transparent antifouling coating and a preparation method thereof", which first disperses fumed silica in a solution, then adds a low surface energy binder to the dispersion, adjusts the pH value to 4-5, then drips the mixed dispersion onto a cloth strip, wipes the glass surface with the cloth strip, and then volatilizes the solvent and solidifies to obtain an antifouling coating. Its preparation process is relatively complicated, and its substrate is a glass sheet, which limits its application on other substrates.
[0005] Chinese patent CN113754308A discloses a method for preparing a super-amphiphobic antifouling transparent coating: first, quadrilateral hollow silica particles are prepared by a sol-gel method, and then mixed with fumed silica to construct a rough structure with concave micropores, and modified with 1H, 1H, 2H, 2H, perfluorodecyltriethoxysilane under the action of a silane coupling agent to obtain a super-amphiphobic antifouling transparent coating. The coating prepared by the invention shows good light transmittance, and at the same time has excellent properties such as super-amphiphobic, self-cleaning, and antifouling. The invention prepares quadrilateral hollow silica particles by a sol-gel method, and its preparation process is relatively complicated. Summary of the invention
[0006] In view of this, in order to solve the above-mentioned technical problems, the purpose of the present invention is to propose an amphiphilic transparent antifouling coating and a preparation method and application thereof. The antifouling coating prepared by the present invention has the characteristics of high optical transparency, good adhesion to the substrate, amphiphilic properties, and excellent antifouling performance.
[0007] The technical solutions adopted are:
[0008] A method for preparing an amphiphilic transparent antifouling coating of the present invention comprises the following steps:
[0009] S1. Select tetramethyl silicate or tetraethyl silicate, and select R1 trimethoxysilane, R2 triethoxysilane, R3, R4 disubstituted dimethoxysilane or R5, R6 disubstituted diethoxysilane, dissolve the two in isopropanol solution, mix and stir to obtain solution A; wherein R1, R2, R3, R4, R5 and R6 are methyl, ethyl, propyl, butyl, hexyl, pentyl, octyl, decyl, anthracenyl, vinyl, chloromethyl, allyl, cycloalkyl, aminopropyl, mercaptopropyl;
[0010] S2. Add a certain concentration of hydrochloric acid or glacial acetic acid or oxalic acid dropwise to solution A and react at room temperature to obtain a uniform, transparent solution B;
[0011] S3. The polyether-modified polydimethylsiloxane was dissolved in another isopropanol solution, and the mixture was mixed and stirred to obtain a solution C;
[0012] S4. Adding solution C to solution B at a controlled rate, reacting at room temperature, to obtain a uniform, transparent solution D;
[0013] S5. The solution D is subjected to ultrasonic dispersion treatment, and then the solution D is coated on the surface of the substrate;
[0014] S6. Place the substrate coated with solution D in a dark place at room temperature to form a uniform coating.
[0015] Furthermore, in S1, 20-80 parts by weight of tetramethyl silicate or tetraethyl silicate, and 20-80 parts by weight of R1-based trimethoxysilane or R2-based triethoxysilane or R3, R4 disubstituted diethoxysilane or R5, R6 disubstituted dimethoxysilane are selected, and both are added to 40-400 parts by weight of isopropanol solution, and solution A is obtained after stirring.
[0016] Furthermore, the amount of hydrochloric acid or glacial acetic acid or oxalic acid used is 1-30 parts by weight, the concentration is 0.1-0.3 mol / L, and the reaction time is 1-12h at room temperature to obtain solution B.
[0017] Further, in S3, 1-50 parts by weight of polyether-modified polydimethylsiloxane is added to 10-50 parts by weight of isopropanol solution to obtain solution C.
[0018] Further, in S4, the solution is added to solution B at a rate of 0.1-2 drops / second, and the reaction is carried out for 12-48 hours to obtain solution D.
[0019] Further, in S5, the ultrasonic dispersion treatment time is 60-300s, and the solution D is coated on the surface of the substrate using a desktop coating machine; the rotation speed of the desktop coating machine is 100-500 rpm, the treatment is 10-60 seconds, and then 1000-3000 rpm, and the treatment is 10-120 seconds.
[0020] Further, in S5, the substrate includes one or more of a glass sheet, a steel sheet, a ceramic sheet, polymethyl methacrylate or polyethylene terephthalate.
[0021] Furthermore, in S6, the coating is placed for 3-21 days.
[0022] The amphiphilic transparent antifouling coating of the present invention is prepared by the above-mentioned preparation method.
[0023] The present invention discloses an amphiphilic transparent antifouling coating for use on the surface of underwater vehicles including visual windows, detection windows, and underwater cameras. The antifouling coating prepared by the present invention can be used for the surface protection of highly transparent equipment such as underwater visual windows, detection windows, and underwater cameras.
[0024] In the above technical solution,
[0025] Technical description of steps S1-S2: In this preparation method, under acidic conditions, selected tetramethyl silicate or tetraethyl silicate is hydrolyzed with selected R1-based trimethoxysilane or R2-based triethoxysilane or R3, R4 disubstituted diethoxysilane or R5, R6 disubstituted dimethoxysilane to generate silicate, and then the silicate is polycondensed to form a silicon-based network to form the basic structure.
[0026] Technical description of step S3: The polyether-modified polydimethylsiloxane used in this preparation method is a type of polymer having both hydrophilic and hydrophobic segments, which gives the coating synthesized by this method an amphiphilic property. Only after the polyether-modified polydimethylsiloxane is fully dissolved can it form a good interpenetration in the silicon-based network formed in S2, and realize the preparation of a uniform and transparent antifouling coating. Polyether-modified polydimethylsiloxane is currently commercially available.
[0027] Technical description of step S4: by controlling the droplet acceleration rate to avoid gelation and precipitation caused by local agglomeration, the reaction is carried out at room temperature for a period of time to ensure that the polyether-modified polydimethylsiloxane can be uniformly interspersed in the formed silicon-based network.
[0028] Technical description of step S5: This preparation method uses ultrasonic dispersion treatment to ensure that the polyether-modified polydimethylsiloxane is evenly dispersed in the system so that a uniform coating structure can be formed in the subsequent coating process.
[0029] Technical description of step S6: In conventional technologies for preparing antifouling coatings, the coating curing conditions basically adopt a high-temperature curing method. However, the curing method of the antifouling coating of this preparation method adopts a room temperature curing method, which avoids the problem of high energy consumption caused by high-temperature curing. At the same time, the rich silanol structure in the prepared coating can form a stable connection with the surface of the substrate, achieving a good adhesion effect with the substrate, and ensuring stability during actual application.
[0030] In summary, compared with the prior art, the present invention has the following advantages:
[0031] 1. The method of the present invention forms a silicon-based network by hydrolysis and polycondensation of selected tetramethyl silicate or tetraethyl silicate and selected alkoxysilane under acidic conditions. However, after the introduction of polyether-modified polydimethylsiloxane, the hydrolysis and polycondensation rates of alkoxysilane in the system need to be carefully regulated, and the problems of gel and precipitation caused by improper procedures are solved by constantly modifying the raw material ratio and the synthesis process. The optimized synthesis method is simple in operation and convenient in process.
[0032] 2. The solvent used in the present invention is a low-volatility solvent and is environmentally friendly.
[0033] 3. The coating prepared by the present invention not only has a suitable surface energy, but also has hydrophilic and lipophilic amphiphilic properties, which can give the coating good antifouling properties.
[0034] 4. The coating prepared by the present invention has good fouling desorption capability and can achieve high amount of fouling desorption under low water flow pressure.
[0035] 5. The amphiphilic transparent antifouling coating provided by the present invention utilizes silicate radicals generated by hydrolyzing selected tetramethyl silicate or tetraethyl silicate and selected R1-based trimethoxysilane or R2-based triethoxysilane or R3, R4 disubstituted diethoxysilane or R5, R6 disubstituted dimethoxysilane under acidic conditions, and then the silicate radicals are connected to form a composite silicon-based network. The coating prepared from the silicon-based network has hydrophobic properties and has a suitable low surface energy. Furthermore, the addition of polyether-modified polydimethylsiloxane can be interspersed in the silicon-based network, giving the coating amphiphilic properties and improving the antifouling performance of the coating.
[0036] 6. The amphiphilic transparent antifouling coating of the present invention can be used for antifouling of underwater visual windows, visual equipment, and camera equipment. The preparation method of the antifouling coating is convenient, the operating conditions are mild, and the solvent used is a low-volatile solvent, which is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The transparency test results of the glass sheet, the coating prepared in Example 1 and the coating prepared in Example 2 under the UV-visible light spectrum are shown.
[0038] Figure 2 This is a graph showing the test results of the water and diiodomethane contact angles of the coating prepared in Example 1. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only partial embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] A method for preparing an amphiphilic transparent antifouling coating of this embodiment comprises the following steps:
[0042] S1. Add 2.08 g of tetraethyl silicate and 2.76 g of n-octyltriethoxysilane to 4 g of isopropanol solution and stir to obtain solution A.
[0043] S2. Add 1.41 g of hydrochloric acid (0.1 mol / L) dropwise into solution A, and react for 1 h at room temperature to obtain solution B.
[0044] S3. Add 0.96 g of polyether-modified polydimethylsiloxane to 2 g of isopropanol solution and stir to obtain solution C.
[0045] S4. Add solution C to solution B at a rate of 0.5 drops / second, react at room temperature for 24 hours, and obtain solution D.
[0046] S5. The obtained solution D was subjected to ultrasonic dispersion treatment for 120 s, with a tabletop homogenizer rotating at 500 rpm for 20 s and then at 2000 rpm for 30 s. 0.4 g of solution D was coated on a 25 mm × 75 mm glass sheet.
[0047] S6. Place the coated glass slide in a dark place at room temperature for 7 days.
[0048] The relevant properties and shapes of the tested coatings are as follows:
[0049] The test result of coating adhesion on steel sheet surface conducted by ASTM D4541-09 standard is: 0.57MPa.
[0050] The blank control sample and the coating sample were placed in a certain concentration of bacterial culture solution for a period of time to allow bacteria to adhere to the surface of the blank control sample and the coating. After the bacteria on the surface of the control sample and the coating were washed off, the number of colonies formed by the bacteria under different surface washes was measured. The number of bacterial colonies grown on the surface of the control sample was set as the standard to calculate the bacterial attachment inhibition rate on the coating surface, and the following data were obtained:
[0051] Antibacterial rate of Pseudoalteromonas Xiamen: 84.0%.
[0052] Antibacterial rate of Escherichia coli: 69.2%.
[0053] Staphylococcus aureus antibacterial rate: 62.9%
[0054] The blank control sample and the coating sample were placed in a certain concentration of diopside algae solution and cultured for 96 hours to allow diatoms to adhere to the surfaces of the blank control sample and the coating. The number of diatoms attached to the surfaces of the control sample and the coating was observed under a microscope. The number of diatoms grown on the surface of the control sample was set as the standard to calculate the diatom attachment inhibition rate on the coating surface, and the following data were obtained:
[0055] The inhibition rate of attachment of Ampelopsis pilosa L. was 63.0%.
[0056] The coating of the above-mentioned D. diatom attachment experiment was placed under a 30Pa water flow for scouring. By comparing the number of D. diatoms attached to the coating surface before and after scouring, the number of D. diatoms attached to the coating surface before scouring was set as the standard for calculating the diatom desorption rate of the coating surface after scouring.
[0057] The desorption rate of D. diffusa under 30Pa water flow is 80.4%.
[0058] The blank control sample and the coating sample were placed in a certain concentration of dichaete algae liquid for 14 days to allow diatoms to adhere to the surface of the blank control sample and the coating. The number of diatoms attached to the surface of the control sample and the coating was observed under a microscope. The number of diatoms grown on the surface of the control sample was set as the standard to calculate the diatom attachment inhibition rate on the coating surface, and the following data were obtained:
[0059] The inhibition rate of attachment of Nitzschia closterium was 75.8%.
[0060] The coating of the diatom attachment experiment was placed under a 30Pa water flow for flushing. By comparing the number of diatoms attached to the coating surface before and after flushing, the number of diatoms attached to the coating surface before flushing was set as the standard to calculate the diatom desorption rate of the coating surface after flushing.
[0061] The desorption rate of Nitzschia closterium under 30Pa water flow is 76.1%.
[0062] The performance of the coating in inhibiting bacterial attachment and diatom attachment demonstrates the application potential of the coating prepared by the method in the field of marine antifouling.
[0063] Example 2
[0064] Referring to Example 1, the difference from Example 1 is that the mass of the polyether-modified polydimethylsiloxane added in S3 of this Example is 0.72 g, and the other steps remain unchanged.
[0065] The relevant properties and shapes of the tested coatings are as follows, and the testing method is the same as in Example 1:
[0066] The test result of coating adhesion on steel sheet surface conducted by ASTM D4541-09 standard is 1.57MPa.
[0067] The antibacterial rate of Pseudoalteromonas Xiamen was 73.4%.
[0068] Antibacterial rate of Escherichia coli: 49.7%.
[0069] Staphylococcus aureus antibacterial rate: 55.7%
[0070] The inhibition rate of attachment of Ampelopsis pilosa L. was 52.8%.
[0071] The desorption rate of D. diffusa under 30Pa water flow is 82.9%.
[0072] The inhibition rate of attachment of Nitzschia closterium was 56.6%.
[0073] The desorption rate of Nitzschia closterium under 30Pa water flow is 89.5%.
[0074] Example 3
[0075] Referring to Example 1, the difference from Example 1 is that the mass of the polyether-modified polydimethylsiloxane added in S3 of this Example is 0.48 g, and the other steps remain unchanged.
[0076] The test result of coating adhesion on steel sheet surface conducted by ASTM D4541-09 standard is: 2.11MPa.
[0077] The relevant properties and shapes of the tested coatings are as follows, and the testing method is the same as in Example 1:
[0078] The antibacterial rate of Pseudoalteromonas Xiamen was 55.3%.
[0079] Antibacterial rate of Escherichia coli: 38.0%.
[0080] Staphylococcus aureus antibacterial rate: 48.0%
[0081] The inhibition rate of attachment of Ampelopsis pilosa L. was 33.7%.
[0082] The desorption rate of D. diffusa under 30Pa water flow is 87.6%.
[0083] The inhibition rate of attachment of Nitzschia closterium was 30.5%.
[0084] The desorption rate of Nitzschia closterium under 30Pa water flow is 94.1%.
[0085] Example 4
[0086] Referring to Example 1, the difference from Example 1 is that the mass of the polyether-modified polydimethylsiloxane added in S3 of this Example is 0.24 g, and the other steps remain unchanged.
[0087] The test result of coating adhesion on steel sheet surface conducted by ASTM D4541-09 standard is: 2.21MPa.
[0088] The relevant properties and shapes of the tested coatings are as follows, and the testing method is the same as in Example 1:
[0089] The antibacterial rate of Pseudoalteromonas Xiamen was 42.2%.
[0090] Antibacterial rate of Escherichia coli: 26.3%.
[0091] Antibacterial rate of Staphylococcus aureus: 31.2%.
[0092] The inhibition rate of attachment of Ampelopsis pilosa L. was 24.0%.
[0093] The desorption rate of D. diffusa under 30Pa water flow is 78.0%.
[0094] The inhibition rate of attachment of Nitzschia closterium was 21.8%.
[0095] The desorption rate of Nitzschia closterium under 30Pa water flow is 84.6%.
[0096] Figure 1 The transparency test results of the glass sheet, the coating prepared in Example 1 and the coating prepared in Example 2 under the UV-visible light spectrum are shown in the figure. According to the results in the figure, it can be seen that in the wavelength range of 350-800nm, the coatings have an optical transparency higher than 95%.
[0097] Figure 2 The test results of water and diiodomethane contact angles of the coating prepared in Example 1 show that the coating has both hydrophilic and lipophilic properties, which proves the amphiphilic properties of the coating and its application potential in the field of marine antifouling coatings.
[0098] The results of the embodiments show that the amphiphilic transparent antifouling coating of the present invention has a light transmittance of 95-99%, has high optical transparency, and can meet the transparency requirements of equipment such as visual windows and underwater camera equipment; the coating has hydrophilic and lipophilic amphiphilic properties; the anti-bacterial adhesion test results show that the anti-fouling coating can inhibit the adhesion of a certain amount of bacteria; the anti-diatom adhesion test results show that the anti-fouling coating can inhibit the adhesion of diatoms and promote the desorption of adhered diatoms under the scouring of a certain pressure water flow.
[0099] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing an amphiphilic transparent antifouling coating, characterized in that: The following steps are involved: S1. Select 20-80 parts by weight of tetramethyl silicate or tetraethyl silicate, and select 20-80 parts by weight of R1 trimethoxysilane, R2 triethoxysilane, R3, R4 disubstituted dimethoxysilane or R5, R6 disubstituted diethoxysilane, both dissolved in 40-400 parts by weight of isopropanol solution, mixed and stirred to obtain solution A; wherein R1, R2, R3, R4, R5 and R6 are methyl, ethyl, propyl, butyl, hexyl, pentyl, octyl, decyl, anthracenyl, vinyl, chloromethyl, allyl, cycloalkyl, aminopropyl, mercaptopropyl; S2. A certain concentration of hydrochloric acid or glacial acetic acid or oxalic acid is added dropwise to solution A, wherein the amount of hydrochloric acid or glacial acetic acid or oxalic acid is 1-30 parts by weight, the concentration is 0.1-0.3 mol / L, the reaction time is 1-12h at room temperature, and a uniform, transparent solution B is obtained; S3. Dissolving 1-50 parts by weight of a polyether-modified polydimethylsiloxane in another 10-50 parts by weight of an isopropanol solution, mixing and stirring to obtain a solution C; S4. Solution C is added to solution B at a controlled rate of 0.1-2 drops / second, and reacted at room temperature for 12-48 hours to obtain a uniform, transparent solution D; S5. The solution D is subjected to ultrasonic dispersion treatment, and then the solution D is coated on the surface of the substrate; S6. Place the substrate coated with solution D in a dark place at room temperature to form a uniform coating.
2. The method for preparing the amphiphilic transparent antifouling coating according to claim 1, characterized in that: In S5, the ultrasonic dispersion treatment time is 60-300s, and the solution D is coated on the surface of the substrate using a desktop coating machine; the rotation speed of the desktop coating machine is 100-500 rpm, the treatment is 10-60 seconds, and then 1000-3000 rpm, and the treatment is 10-120 seconds.
3. The method for preparing the amphiphilic transparent antifouling coating according to claim 1, characterized in that: In S5, the substrate includes one or more of a glass sheet, a steel sheet, a ceramic sheet, polymethyl methacrylate, and polyethylene terephthalate.
4. The method for preparing the amphiphilic transparent antifouling coating according to claim 1, characterized in that: In S6, the coating is placed for 3-21 days.
5. An amphiphilic transparent antifouling coating, characterized in that: The invention is prepared by the preparation method described in any one of claims 1 to 4.
6. Use of the amphiphilic transparent antifouling coating according to claim 5 on the surface of equipment including visual windows, detection windows, and underwater cameras of underwater vehicles.
Citation Information
Patent Citations
Transparent antifouling coating material used for glass, and transparent antifouling coating and preparation method thereof
CN105152546A
Transparent marine anti-fouling paint as well as preparation method and application thereof
CN113004752A
Preparation method of super-amphiphobic antifouling transparent coating
CN113754308A
Triphenylboron compound-containing antifouling coating composition having improved stability, antifouling agent set used therefor, and method for suppressing / controlling decomposition of triphenylboro
CN101652444A
Anti-doodling paint and preparation method thereof
CN109401616A